Communicating Branches of the Facial Nerve: Descriptions and Clinical Considerations. (11th February 2022) - Freed, Blair; Coker, Charles; Steele, Robert; Marolt, Clayton; Motzko, Micaela; Creamer, Bradley A; Dennis, Jennifer F
Abstract: Background: Major branching patterns of the facial nerve have been extensively studied because damage to branches of the nerve is associated with complications ranging from weakness to paralysis. However, communicating branches of the facial nerve have received far less attention despite being hypothesized as a means of motor recovery following facial nerve injury. Objectives: The aim of this study was to characterize the frequency of communicating branches of the facial nerve to provide clarity on their anatomy and clinical correlations. Methods: Bilateral facial dissections were completed on cadaveric donors (n = 20) to characterize the frequency and location of communicating branches across terminal branches of the facial nerve. Statistical analyses were employed to analyze differences between the location of communications by side and whether the communicating branches were more likely to occur on the left or right side ( P < 0.05). Results: Communicating branches were identified among all terminal branches of the facial nerve and their frequencies reported. The highest frequencies of communicating branches were identified between the buccal-to-marginal mandibular and zygomatic-to-buccal branches, at 67.5% (27 comm/40 hemifaces). The second highest frequency was identified between the temporal-to-zygomatic branches in 62.5% (25/40) of donors. The marginal mandibular-to-cervical branches had communicating branches at a frequency of 55% (22/40). Location or sidedness of communicating branches did not significantly differ. Conclusions: Our characterization more accurately defines generalizable areas in which communicating branches are located. These locations of branches, described in relation to nearby landmarks, are fundamental for clinical and surgical settings to improve procedural awareness.